Dense Hierarchy Decomposition for Bipartite Graphs - Moreira, Edré; Campos, Guilherme Oliveira; Meira Jr., Wagner (Anais do Symposium on Knowledge Discovery, Mining and Learning (KDMiLe); 2019: Anais do VII Symposium on Knowledge Discovery, Mining and Learning, 2019)
Dense subgraphs detection is a well known problem in Computer Science. Hierarchical organization of graphs as dense subgraphs, however, goes beyond simple clustering as it allows the analysis of the network at different scales. Despite the fact there are several works on hierarchical decomposition for unipartite graphs, only a few works for the bipartite case have been proposed. In this work we explore the problem of hierarchical decomposition of bipartite graphs. We propose an algorithm which we call weighted linking that produces denser and more compact hierarchies. The proposed algorithm is evaluated experimentally using several datasets and provided gains on most of them.